2008
DOI: 10.1177/0961203307088289
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin prevents the development of nephritis in lupus-prone NZB/W F1 mice

Abstract: Rapamycin is a potent immunosuppressive drug currently used mainly for rejection prophylaxis in renal transplantation. The aim of this study was to determine the effect of rapamycin treatment on the development of nephritis in lupus-prone New Zealand Black/White F1 (NZB/W F1) mice. Twelve-week-old female NZB/W F1 mice were treated with rapamycin (3 mg/kg body weight) or saline once daily by oral gavage for 20 weeks. The severity of nephritis was assessed by clinical and biochemical parameters, renal histology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 34 publications
4
34
0
2
Order By: Relevance
“…Similarly, whereas rapamycin treatment alleviates lupusassociated symptoms associated with autoantibody production in NZB/W mice (23,24), the underlying mechanisms remain poorly defined. Consistent with past work, treatment of symptomatic NZB/W mice with rapamycin twice weekly not only reduced proteinuria to background levels within 6 weeks ( Figure 1A), but also caused a sharp decline in anti-dsDNA serum IgG antibodies (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, whereas rapamycin treatment alleviates lupusassociated symptoms associated with autoantibody production in NZB/W mice (23,24), the underlying mechanisms remain poorly defined. Consistent with past work, treatment of symptomatic NZB/W mice with rapamycin twice weekly not only reduced proteinuria to background levels within 6 weeks ( Figure 1A), but also caused a sharp decline in anti-dsDNA serum IgG antibodies (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibiting mTOR activity thwarts the generation of Th1 and Th17 effector T cells (21), but perhaps paradoxically can also enhance frequencies of cytotoxic T cells (22). Moreover, rapamycin treatment prevents and reverses lupuslike symptoms in (NZB×NZW)F 1 (NZB/W) mice (23,24), and this effect has been attributed mainly to the critical role played by mTOR signaling in effector T cell differentiation (25).…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of its immunosuppressive mechanisms, it is speculated that sirolimus can also serve as a potential therapy for LN. In this context, previous animal studies from our group and other investigators have demonstrated that sirolimus could delay the onset of renal manifestations and could also ameliorate established nephritis in NZB/W F1 mice [16][17][18][19]. Early studies have reported that sirolimus could improve disease activity scores in 9 active SLE patients (2 with renal involvement) who were refractory to standard immunosuppressive treatments [20].…”
Section: Introductionmentioning
confidence: 89%
“…Possible mechanisms leading to a reduction of disease activity include reduction of intra-renal lymphoproliferation and MCP-1 expression, suppression of anti-dsDNA production and immune deposition, reversal of senescent phenotype of bone marrow-derived mesenchymal cells, promotion of Treg expansion and blockade of Th17 expansion [16][17][18][27][28][29][30]. Furthermore, the results from animal experiments and human kidney biopsies demonstrating activation of the mTOR pathway during active nephritis, and the therapeutic effect of mTOR inhibitor in murine lupus, provide a strong rationale for testing the effect of mTOR inhibitors in the treatment of human LN [16,17]. In this regard, previous studies have shown that mTOR activity was increased in lupus T cells, and rapamycin treatment reversed TCRzeta deficiency and FcepsilonR1gamma upregulation, which underlied aberrant T cell activation and death pathway selection in SLE [31].…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Rapamycin has been used as an immunosuppressive agent and several reports have shown that rapamycin decreased the development of glomerulonephritis in NZB/W and MRL/lpr mice. [70][71][72][73] Although inhibition of mTOR has been shown to exert beneficial effects in lupus mice, other reports have suggested a negative outcome with the use of rapamycin in regulating anti-GBM glomerulonephritis, depending on timing of administration. 74 mTOR blockage by rapamycin has also been shown to induce proteinuria and renal deterioration and induce focal segmental glomerulonephritis.…”
Section: Egcg Inhibits Inflammation In Lupus Mesangial Cells a Peairsmentioning
confidence: 99%